URGENSI PROFESI ADVOKAT DALAM PENEGAKAN HUKUM DI INDONESIA - Raden Muyazin Arifin (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2017)
Advocate in Law number 18 of 2003 on advocates, is a Law Enforcement that is equal with other Law Enforcers, such as Police, Prosecutors and Judges. As a Law Enforcer, advocates in carrying out their duties are framed with a code of ethics in order to advocate professionals in carrying out their duties. In order to carry out their duties and functions, Advocates are always struggling to reach the truth, justice, liberty and equality for their clients so as not to be impeded in the legal process in their path. In international agreements, as noted in the Basic Principles on the Role of Lawyers (Adopted by Eighth Crime Congress, 1990), international recognition of the importance of legal counsel may be seen. Within this international document are stipulated principles proving how important the position of legal counsel in the criminal justice system. The success of law enforcement is in fact also influenced by the roles and responsibilities of legal advisory groups. A quick, simple and honest judgment is not solely aimed at four commonly recognized components of law enforcement, but is also addressed to legal advisory groups as the fifth component.